Online existential-phenomenological psychological counseling as an option of psychological attention during the COVID-19 pandemic - Evangelista, Paulo Eduardo Rodrigues Alves (2021)
The COVID-19 pandemic interrupted face-to-face activities in almost all areas of psychological care. The first studies on psychological impacts indicate existential sufferings such as fear and panic, stigmatization, exclusion, and depression. We try for an understanding of this moment based on the existential-phenomenological perspective as a rupture of daily familiarity that casts existence in its indetermination and in search of ways to stabilize itself. Thus, we present phenomenological-existential psychological counseling as a modality of psychological care focused on mental health prophylaxis that aims at greater clarity in the existential situation currently experienced in order to have greater freedom to deal with the new daily life. As face-to-face activities are interrupted, psychological counseling by online communication tools is explored as an alternative to this moment, supported by literature on such practice.